Iterative algorithm for solving the retrospective problem of natural thermal convection of a viscous fluid - Tsepelev, Igor Anatolievich (Computational Continuum Mechanics, 2011)
A retrospective problem consisting in the recovery of a priori unknown initial state of a viscous incompressible fluid on the basis of its known final state is investigated. A fluid dynamics model in the Boussinesq approximation is described by Stokes, incompressibility and thermal balance equations under corresponding initial and boundary conditions. To solve the problem in reverse time, a new iterative approach has been developed in which the unstable initial problem is reduced to a series of stable problems. An algorithm, obtained using the proposed approach, is implemented on the parallel computer in OpenFOAM. The results show the computational efficiency of the developed algorithm.
Keywords: Stokes equation; retrospective problem; viscous fluid flows; finite volume method; ill-posed problem; natural thermal convection; incompressible flow; engineering software packages